Pola Interaksi Ruang Kegiatan Usaha Perikanan Tangkap Desa Bajomulyo, Kecamatan Juwana, Kabupaten Pati - Novia Rini Listiana; Djoko Suwandono (Jurusan Perencanaan Wilayah dan Kota, 2021)
Pati Regency is a regency in Central Java which has abundant natural wealth, one of which is in the potential capture fisheries sub-sector. Capture fisheries business in Pati Regency which is very potential is located in Bajomulyo Village, Juwana District. Bajomulyo Village is synonymous with the term